Характеристика сортов разных этапов селекции в России и селекционных линий яровой твердой пшеницы по качеству клейковины - P. N. Malchikov; M. A. Rozova; E. N. Shabolkina; M. G. Myasnokova; I. V. Fomina; V. I. Tsygankov (Зерновое хозяйство России, 2018)
The characteristics of the cultivars of various stages of breeding process in Russia and the selective lines of spring durum wheat according to quality of gluten The present highly productive technological industries of pasta products that apply thermal drying need grain of durum wheat with strong and high qualitative gluten. Thus, the principle purpose of the study is to estimate the cultivars of various stages of breeding and the selective lines of spring durum wheat according to quality of gluten and to seek adapted genes that can produce high qualitative gluten. There have been studied such varieties of different breeding centers and of different stages of breeding process as ‘Kharkovskaya 46’ (4-th stage), ‘Bezenchukskaya 139’, ‘Altayskaya niva’ (5-th stage), ‘Bezenchukskaya 182’, ‘Saratovskaya zolotistaya’, ‘Zhemchuzhina Sibiri’, ‘Altaysky yantar’, ‘Omsky korund’ (6-th stage), ‘Bezenchukskaya stepnaya’, ‘Bezenchukskaya 205’, ‘Krasnokutka 13’, ‘Donskaya elegiya’, ‘Bezenchukskaya niva’, ‘Bezenchukskaya 209’, ‘Bezenchukskaya 210’, ‘Bezenchukskaya zolotistaya’, ‘Luch 25’, ‘Bezenchukskaya krepost’, ‘Zolotaya’, ‘Salyut Altaya’, ‘Solnechnaya 573’, ‘Pamyati Yanchenko’, ‘Omsky izumrud’, ‘Oazis’ (7-th stage) and such breeding lines as ‘D2098’, ‘98с-08’ (RIA of South-East), ‘Gordeiforme 677’ (Altaysky RIA), ‘1368D-18’, ‘1477D-4’ (Samarsky RIA). The study has been made in two ecological-geographical experiments, the first one in the areas of Bezenchuk, Kurgan and Barnaul (in 2014-2015) and the second one in the areas of Bezenchuk, Barnaul and Aktyubinsk (in 2016). The plots of 10 m2 were placed in random sequences in fallow lands. The simplest and productive method of SDS-sedimentation was used to estimate the rheological traits of dough. The SDS indexes were assessed by a standard method [8]. The rheological traits of the varieties grown by Samarsky RIA in 2015 have been assessed by the parameters of farinograph according to the international standards. The conducted study has found that the varieties of the 7-th stage of breeding process (‘Bezenchukskaya 209’, ‘Zolotaya’ and ‘Luch 25’) and the breeding lines of the South-East RIA (‘D2098’, ‘98c-08’) produce high qualitative gluten (according to SDS test and parameters of microfarinograph). The genotypes of ‘Bezenchukskaya 209’, ‘Zolotaya’ and ‘D2098’ have been found highly stable in the production of the studied trait. The area of Kurgan has been found predictable in weather and climatic conditions.